First philosophy in Books E and Λ of Aristotle’s Metaphysics - Stoll, Renan Eduardo (Revista Archai, 2026)
In this paper, I analyze three conditionals present in Books E and Λ of Aristotle’s Metaphysics. The conditionals in Book E correspond to passages 1026a10-13 and 1026a29-32, while the conditional in Λ corresponds to passage 1069a36-b2. I consider that the way we interpret the implications of these conditionals may generate a tension regarding the nature of first philosophy and its subject. To dissipate this possible tension, I suggest that, for Aristotle, the scope of first philosophy would not be restricted to separate and immovable things, and I propose, from this perspective, two ways in which sensible substances can be considered.